Effect of Young Coconut Water Concentration on The Growth of Dendrobium Orchid Seedlings - Irmayanti, Amanda; Prasetiyo, Prasetiyo; Rahayu, Praptining (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to assess the effect of young coconut water concentration on the growth of Dendrobium orchids. The research was conducted for 4 months at Candi Orchid Production House, Semarang, with a one-factor completely randomized design (CRD) and four treatments of young coconut water concentration (0 mL/L, 100 mL/L, 150 mL/L, 200 mL/L), each with five replications. Parameters observed included number of shoots, root length, and plant height. Data were analyzed using ANOVA and Duncan's further test at the 5% level. The results showed that the application of young coconut water had no significant effect on the number of shoots and root length (p > 0.05), but had a significant effect on plant height (p = 0.003), especially at a concentration of 100 mL/L. The predominance of cytokinin hormones in coconut water likely plays a role in stimulating stem growth, while its effects on shoots and roots require interactions with other hormones. Although coconut water contains essential nutrients, its composition may not be fully suitable for the physiological needs of orchids in the seedling phase.